PERAN STRATEGI COPING DAN DUKUNGAN SOSIAL ORANG TUA TERHADAP STRES AKADEMIK MAHASISWA TUGAS AKHIR: The Role of Coping Strategies and Parental Social Support on Final Project Students Academic Stress - Mamo, Semarlin Oktoviana; Nggeong, Fransiska; Amseke, Fredericksen Victoranto (Yayasan Al-Amin Qalbu, 2025)
Student academic stress is very important as the body's response to facing academic demands, in this case the demand to complete a final assignment or thesis as a stressful experience which becomes a strength within the student to be managed well. Academic stress is influenced by coping strategies and parental social support as external factors. This research uses quantitative methods. Data collection tools used a coping strategy scale, parental social support scale and academic stress scale. The participants in this research were 78 students in the Christian Religious Education study program at the Kupang State Christian Religion Institute. The data analysis technique uses multiple regression analysis. The results of this research prove that coping strategies and social support have a positive and significant effect on students' academic stress in completing their final assignments by 46.6%. Coping strategies contributed 20% and parental social support contributed 26.6% to students' academic stress in completing their final assignments. The higher the coping strategies and the role of positive social support from parents, the more it can increase students' academic stress as a strength to manage academic stress in doing their final assignments well.